2019
DOI: 10.1007/s00125-019-4829-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous ketonuria and risk of incident diabetes: a 12 year prospective study

Abstract: Aims/hypothesis Ketones may be regarded as a thrifty fuel for peripheral tissues, but their clinical prognostic significance remains unclear. We investigated the association between spontaneous fasting ketonuria and incident diabetes in conjunction with changes in metabolic variables in a large population-based observational study. Methods We analysed 8703 individuals free of diabetes at baseline enrolled in the Korean Genome and Epidemiology Study, a community-based 12 year prospective study. Individuals with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 62 publications
0
19
1
Order By: Relevance
“…In a remarkable study of healthy people, ketonuria after spontaneous (overnight) fasting was associated with a reduced risk of diabetes. Indeed, Kim et al suggested that spontaneous ketosis may prevent the development of diabetes [100]. Ketogenesis is suppressed in aged mice and rapamycin increases ketone production [101].…”
Section: Benevolent Pseudo-diabetes Prevents Type 2 Diabetesmentioning
confidence: 99%
“…In a remarkable study of healthy people, ketonuria after spontaneous (overnight) fasting was associated with a reduced risk of diabetes. Indeed, Kim et al suggested that spontaneous ketosis may prevent the development of diabetes [100]. Ketogenesis is suppressed in aged mice and rapamycin increases ketone production [101].…”
Section: Benevolent Pseudo-diabetes Prevents Type 2 Diabetesmentioning
confidence: 99%
“…Pathological ketosis occurs in uncontrolled DM and hyperglycemia due to insufficient insulin production, and is associated with life threatening conditions, such as diabetic ketoacidosis [12]. However, nutritional ketosis, associated with prolonged fasting and low carbohydrate or ketogenic diets (KD), has been shown to be metabolically favorable in recent studies [13][14][15][16]. In a recent study, KD was shown to have hepatic antisteatotic effects by the activation of mitochondrial beta oxidation in patients with NAFLD [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a 12 year longitudinal study in Korea, the relationship between the presence of spontaneous fasting ketonuria was associated with a low risk of DM (HR, 0.63; 95% CI, 0.41–0.97) and subjects with ketonuria show lower glucose level after loading of glucose. 23 We already have reported the results that the healthy obese group with the presence of ketonuria get more reduction in body weight, BMI, and waist circumference compared to the non-ketonuria group. 24 In one study conducted during the Muslim fasting period, most of the obese individuals did not show ketonuria after more than 20 days of fasting, on the other hand, the normal weight group showed ketonuria after 3–6 days of fasting.…”
Section: Discussionmentioning
confidence: 88%